Efficacy and safety of Chinese herbal medicine Long Dan Xie Gan Tang in insomnia: A systematic review and meta-analysis. Issue 11 (March 2020) - Fan, Xu; Su, Zhuang; Nie, Shichao; Yang, Jie; Zhang, Xiaoyu; Tan, Dongyang; Xie, Sihang; Xu, Yi; Zhao, Yanying; Feng, Liu; Gu, Mingyi; Sun, Xiaomeng
Abstract: Background: Insomnia is a global public problem, which has a significant negative impact on both physical and mental health, while increasing the economic burden placed on both sufferers and society. Western medicine has a fast treatment on sleep, but it leads to side effects and strong dependence. Long Dan Xie Gan Tang(LDXGT) is a representative Chinese herbal medicine for the treatment of insomnia especially which has a bad-tempered symptom, and its effectiveness and safety has been validated clinically. However, there is yet to be any evidence-based medicine. Therefore, the effectiveness and safety of LDXGT in the treatment of insomnia are studied and systematically evaluated in this study. It will provide a theoretical support for the treatment of insomnia compared to western medicine. Objective: The study is purposed to evaluate the effectiveness and safety of LDXGT for the treatment of insomnia. Methods: Search was conducted for various databases including Pubmed, Chinese Biomedicine Database(CBM), China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), and Wan-fang. Randomized-controlled trials (RCTs) were identified for insomnia treatment involving LDXGT and LDXGT combined with ordinary Western medicine. The quality of literature was evaluated by Cochrane assessing tool to reduce the risk of bias. RevMan 5.3 software and STATA 12.0 software were applied to perform the meta-analysis. Results: Thirteen studies involving 1181 participants were identified in this systematic review. Few studies described the details of random principle. No placebo was involved in treatment. LDXGT was compared with ordinary Western medicine in 11 trials and with LDXGT combined with conventional Western medicine in 2 trials. The results of our meta-analysis showed the relative benefits in effective rates compared with conventional western medicine. (Odds Ratio [OR]= 4.32, I 2  = 0%, 95% confidence interval CI [3.05 to 6.13], P  < .00001) and recovery rate was (Odds Ratio [OR] = 2.67, I 2  = 0%, 95% confidence interval CI [2.04 to 3.48], P  < .00001). In two trials, adverse events were reported, but no serious adverse effects were reported. Conclusion: Our systematic evaluation will provide evidence for the clinical effectiveness and safety of LDXGT in the treatment of insomnia, and the side effects of western medicine are addressed. Further trials are necessary to collect the evidence for the use of LDXGT.